Pengaruh Framing Informasi dan Gaya Kognitif terhadap Proses Revisi Keyakinan dalam Keputusan Akuntansi Manajemen - , Wulandari Fitri E ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the important roles of management accountants, nowadays, is to provide input for managers in decision making. The presentation order of the input and response modes used, either sequentially or simultaneously, can lead to order effects (either primacy or recency) that resulted in the bias decision making. Order effects in this study were analyzed using the Belief-Adjustment Model (Hogarth and Einhorn, 1992). This study aims to empirically examine the moderating influence of information framing and cognitive style toward belief revision process in management accounting decision, namely budgeting preparation. Laboratory experimental method used in this study with a 2x2x2 between-subjects design and participants consisted of 86 undergraduate accounting students of University of Muhammadiyah Magelang and the 14 Accounting Profession students of Gadjah Mada University. The results of this study indicate that in the Step-by-Step (sequentially) response mode, the occurence of recency effects can be mitigated by information framing. In contrast, in the End-of-Sequence (simultaneously) response mode did not reveal any order effects. Moreover, there is quite interesting finding that there is interaction effect between information order and response modes reflecting that the End-of-Sequence response mode can be one of the solutions to reduce the recency effects. However, this study did not find an interaction effect between information order, information framing, and cognitive styles, both in Step-by-Step and End-of-Sequence response mode. Keywords: Order effects, Belief-Adjustment Model, Framing, Cognitive style